Beyond coercion: developing post-coercive practice support for mental health inpatients, a modified e-Delphi consensus process - Lewys Beames; Alan Simpson; Juliana Onwumere (BMC Psychiatry, 2026)
Abstract Background Exposure to coercive practices in mental healthcare is associated with a range of patient harms. Clinical guidelines recommend that patients exposed to coercive practice in inpatient settings are offered support, however, existing post-coercive practice support models are often limited to debrief approaches, lack clear operationalisation, and have not integrated lived experience perspectives in their design. There remains a lack of clarity regarding the aims, optimal delivery approaches, core components and preferred personnel of such interventions. This consultation therefore aimed to determine areas of consensus and disagreement on the components and structure of a post-coercive practice support intervention for mental health inpatients. Methods A consultation employing a three-round modified e-Delphi process was conducted with an expert panel of patients, family/carers, and mental health staff in the United Kingdom. Survey items comprised aims, delivery approaches, components and personnel for a patient post-coercive practice support intervention. In Round 1 experts rated importance of components; in Round 2 items were sequenced across three time points (immediate, intermediate and post-discharge); and in Round 3 the experts finalised a component checklist. Quantitative data were analysed descriptively, while qualitative data were analysed using reflexive thematic analysis. Consensus was defined a priori as agreement among ≥ 75% of the panel. Triangulation of quantitative and qualitative findings informed the final component checklist. Results Consensus was reached on 39 intervention components. Following triangulation, a phased support framework was developed comprising 30 components in an immediate support phase, 18 in a later intermediate inpatient phase, and 4 in a post-discharge phase. Findings indicate distinct aims and components across the phases. In the early support phase patient safety and psychological stabilisation were prioritised. In the intermediate phase sharing of perspectives, mutual understanding and prevention of further coercive practice were prioritised. Consensus regarding the post-discharge phase was more limited and consequently remains underdeveloped. Conclusions Findings suggest post-coercive practice support should be conceptualised as a multi-phase process rather than a singular debrief intervention. The resulting lived-experience-informed component checklist provides a framework for the operationalisation and feasibility testing of an inpatient post-coercive practice support intervention.